The impact of a heat therapy intervention on pain and fibromyalgia symptoms in patients with fibromyalgia: a pilot study - Chadwick, Andrea L.; Shi, Chloe; McMillan, Miranda; Miller, Josh; Hu, Jinxiang; Geiger, Paige C. (Frontiers in Pain Research, 2025)
IntroductionFM is characterized by widespread musculoskeletal pain and associated somatic symptoms including fatigue, cognitive difficulties, and problems with sleeping. Multidisciplinary treatment of fibromyalgia including pharmacologic and non-pharmacologic interventions are recommended to improve symptoms and physical functioning. The goal of the present pilot investigation was to evaluate the effects of heat therapy via hot water immersion on clinical and objective pain measures in addition to blood measurements of heat shock proteins (HSPs) and inflammatory markers in patients with FM.MethodsAfter screening, informed consent, and enrollment into the study, all subjects underwent a baseline pre-intervention evaluation which included a battery of pain phenotyping questionnaires, quantitative sensory testing, and collection of blood for measurements of HSPs and inflammatory markers. Subjects received heat therapy three times a week for four weeks, where they were immersed in hot water for 45 min. After four weeks, participants completed the same battery of testing done at baseline.ResultsWe found that four weeks of heat therapy via hot water immersion in patients with FM showed statistically significant reductions in average and worst pain NRS severity scores when compared to baseline. There was also statistically significant improvement in overall impact of fibromyalgia symptoms, physical function, and sleep-related impairment. Regarding heat shock proteins, there was a statistically significant reduction in HSP90 and induction of HSP40 and HSC70. The number of extracellular vesicles were also statistically significantly increased. There were no statistically significant changes found in depression, anxiety, quantitative sensory testing measures, or pro- or anti-inflammatory markers.ConclusionsAs a whole, these findings suggest that heat therapy via hot water immersion may be an effective non-pharmaceutical intervention for patients with FM and that its analgesic benefits may be related to decreases in HSP 90 and increases in HSP 40 and 72. Further large-scale, well-powered studies are needed to confirm our preliminary clinical and translational results.